A computerized database for freshwater algae recorded in Turkey - Şen, Bülent; Alp, Mehmet Tahir; Sönmez, Feray; Aykulu, Güler; Yildiz, Kazim (My University, 2006)
A computer-based database for freshwater algae recorded in Turkey has been established. The first phase of the project involved the selecting of data types available for freshwater algal species occurring in Turkey. Such data were obtained from algal studies previously carried out in various freshwater bodies of the country. Data were then standardized in accordance with "The Central Database of Turkish Herbaria". The database program Access was used for entering data, as this program recognises Turkish characters. Algal data were entered into the database in the following order: division, class, order, family, genus, species, species author, subspecies, subspecies author, variety, variety author, province, and locality. More than 6000 pieces of data were loaded into the database. © TÜBİTAK.
Keywords: Database; Freshwater algae; Turkey